Emotional political advertising - Lynnette Fourie; Johannes Froneman (Communicare)
The real possibility exists that the overemphasis of a party’s image in advertisements could lead to the neglect of important political information for voters. Emotional and negative advertisements could therefore be detrimental to any young democracy. Against this background this article investigates the use of emotional persuasive appeals and negative messages in political newspaper advertisements in the North-West Province during South Africa's general elections in 1999. The results indicate that although all the parties in the study used emotional appeals, they mostly connected them to a policy issue. However, these policy issues were not elaborated on. The opposition parties mostly used appeals of uncertainty, fear and rage. The ruling party in the province (the ANC) concentrated on appeals of hope and achievement. The ANC virtually abstained from using negative messages, while the DP, the NNP and the FF "attacked" one another in order to emphasise their differences. They did not harm the sustainability of the South African democracy as such, but they also did very little to promote it actively through their media advertisements.